Analysis of Student Errors In Solving Story Problems Based on Newman's Stage In Class VII - Timbul Yuwono; Yublina Rambu; Sumadji Sumadji (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
This study aims to describe the mistakes of students based on the Newman stage in solving the story problems of the One Variable Linear Equation material. This type of research is qualitative descriptive with a descriptive approach. The subjects of this study were 34 students of class VII-F SMP Negeri 17 Malang, consisting of 20 boys and 14 girls for the 2019/2020 school year. Research subjects 30 subjects from class VII-F students were present for analysis. Retrieval of data using written tests to obtain data about students 'mistakes in solving story questions based on Newman stages and interviews to complete the results and strengthen data about students' mistakes. Data analysis techniques include data reduction, data presentation and drawing conclusions. Checking the validity of the data used the source triangulation technique in the form of interviews with 3 students of class VII-F who were selected based on high, medium, and low abilities. Based on the results of the study, it appears that the mistakes made by students based on the Newman procedure, at the reading stage there were no research subjects who made mistakes. At the understanding stage there were 23 subjects who made mistakes, the transformation stage there were 30 subjects who made mistakes, the process skills stage there were 17 subjects who made mistakes and the final answer writing stage there were 29 subjects who made mistakes. The results showed that all students made four types of errors. The causative factor is that there are certain sentences in the questions that cannot be interpreted correctly, forgetting the formulas that must be used, rushing when writing formulas, not mastering the material of One Variable Linear Equations, not being thorough and in a hurry to do the problems.